Varied clinical presentation of compound heterozygous thalassemia with delta beta or hereditary persistence of foetal hemoglobin - Sneha Waghela; Sujata Sharma; Nikita Shah; Harshada Uchil; Radha Ghildiyal (Elsevier, 2023)
Introduction: Delta-beta thalassemia and hereditary persistence of fetal hemoglobin (HPFH) results from a deletion in both the delta and beta genes on chromosome 11. Heterozygous/Homozygous delta-beta thalassemia and HPFH have a varied clinical features including age of presentation, transfusion requirement and mild to severe anemia. Aim: To study the clinical profile of patients with compound heterozygous delta beta thalassemia/HPFH. Methods: Retrospective analysis of 5 patients diagnosed as compound heterozygous delta-beta thalassemia/HPFH and followed up in the tertiary care hospital. The diagnosis was done by High Performance Liquid Chromatography (HPLC) of the patients and their parents. The data was collected from medical records of the hospital. Results: Five patients diagnosed as compound heterozygous delta-beta thalassemia/HPFH on HPLC were studied, of which 3 were males and 2 females. The mean age was 7.6 years (range 2-15). All patients had pallor and spleno-hepatomegaly at presentation. The mean hemoglobin at presentation was 6.14 gm% (range 4.2-9.2) with peripheral smear suggestive of thalassemia like picture. Mutation studies were available for 4 patients. Three patients were transfusion independent; 2 were on transfusion regimen. Conclusion: Compound heterozygous delta-beta thalassemia/HPFH has varied clinical features with severity ranging from non-transfusion dependent to transfusion dependent. As there is limited literature on compound heterozygous delta-beta thalassemia/HPFH, such cases need to be identified and reported.